Systemic tryptophan homeostasis - Klaessens, Simon; Stroobant, Vincent; De Plaen, Etienne; Van den Eynde, Benoit J. (Frontiers in Molecular Biosciences, 2022)
Tryptophan is an essential amino acid, which is not only a building block for protein synthesis, but also a precursor for the biosynthesis of co-enzymes and neuromodulators, such as NAD/NADP(H), kynurenic acid, melatonin and serotonin. It also plays a role in immune homeostasis, as local tryptophan catabolism impairs T-lymphocyte mediated immunity. Therefore, tryptophan plasmatic concentration needs to be stable, in spite of large variations in dietary supply. Here, we review the main checkpoints accounting for tryptophan homeostasis, including absorption, transport, metabolism and elimination, and we discuss the physiopathology of disorders associated with their dysfunctions. Tryptophan is catabolized along the kynurenine pathway through the action of two enzymes that mediate the first and rate-limiting step of the pathway : indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan 2,3-dioxygenase (TDO). While IDO1 expression is restricted to peripheral sites of immune modulation, TDO is massively expressed in the liver and accounts for 90% of tryptophan catabolism. Recent data indicated that the stability of the TDO protein is regulated by tryptophan and that this regulation allows a tight control of tryptophanemia. TDO is stabilized when tryptophan is abundant in the plasma, resulting in rapid degradation of dietary tryptophan. In contrast, when tryptophan is scarce, TDO is degraded by the proteasome to avoid excessive tryptophan catabolism. This is triggered by the unmasking of a degron in a non-catalytic tryptophan-binding site, resulting in TDO ubiquitination by E3 ligase SKP1-CUL1-F-box. Deficiency in TDO or in the hepatic aromatic transporter SLC16A10 leads to severe hypertryptophanemia, which can disturb immune and neurological homeostasis.